2013
DOI: 10.1007/s10156-012-0454-z
|View full text |Cite
|
Sign up to set email alerts
|

The definition of healthcare-associated pneumonia (HCAP) is insufficient for the medical environment in Japan: a comparison of HCAP and nursing and healthcare-associated pneumonia (NHCAP)

Abstract: Healthcare-associated pneumonia (HCAP) is a new concept of pneumonia, which was proposed in ATS/IDSA guidelines. The guidelines explain that HCAP patients should be treated with broad-spectrum antimicrobial drugs directed at multidrug-resistant (MDR)-pathogens. However, in Japan, there are many elderly people who received an in-home care service. They seemed to be consistent with the concept of HCAP, but they didn't meet the definition of HCAP. Therefore, the Japanese Respiratory Society modified the definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…In 2010, the acute hospitalisation rate, standardized for age and gender, was around 115 per 1000 inhabitants, and respiratory diseases are among the most prevalent causes of hospitalisation in the elderly [23]. On the other hand, in Japan, there are many elderly people who receive in-home care services [24]. In the United States, there is a mixed system, containing elements of both traditional sickness insurance and national health coverage [5].…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, the acute hospitalisation rate, standardized for age and gender, was around 115 per 1000 inhabitants, and respiratory diseases are among the most prevalent causes of hospitalisation in the elderly [23]. On the other hand, in Japan, there are many elderly people who receive in-home care services [24]. In the United States, there is a mixed system, containing elements of both traditional sickness insurance and national health coverage [5].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous reports have indicated that performance status (PS) evaluation is useful for predicting the outcome of patients with pneumonia (19,20). Therefore, PS is one of the criteria of nursing and healthcare-associated pneumonia (NHCAP), which was newly categorized in the 2011 Japanese Respiratory Society guidelines (6,21). Although PS could not be documented from the medical records in the present study, our results, which focus on ADL dependency, correspond with the concept of NHCAP which includes patients with diminished PS in addition to HCAP patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the HCAP population is heterogeneous and overlaps with that of community-acquired pneumonia (CAP) in the elderly (4)(5)(6). Additionally, physical functional status is not included in the HCAP definition, even though it is a crucial predictor of drug-resistant pathogens and patient outcome (4,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…A number of Japanese studies have compared nursing-and health care-associated pneumonia with CAP because this category was introduced by the Japanese Respiratory Society in 2011. 65,[68][69][70][71] The studies showed that nursing-and health careassociated pneumonia is in general comparable with HCAP in terms of a trend to increased frequency of drug-resistant pathogens and increased mortality compared with CAP. However, similar to HCAP, none of these studies did show a link between inappropriate initial antibiotic treatment and increased mortality.…”
Section: Hcap In the Asia-pacific Regionmentioning
confidence: 99%